Assessment of knowledge and attitude of healthcare professionals regarding the use of telemedicine: A cross-sectional study from rural areas of Sindh, Pakistan - Kumar, Grouve; Shardha, Harsha Komal; Tariq, Waleed; Qazi, Mansoor Ahmed; Kumar, Kantesh; Maheshwari, Chandni; Hussain, Atif; Tahir, Muhammad Junaid; Bai, Jharna; Asghar, Muhammad Sohaib (Frontiers in Public Health, 2022)
Background: Telemedicine has proved its significance in healthcare system especially in the COVID-19 pandemic as it assists the provision of early and effective healthcare to distant areas. The purpose of this study is to assess the knowledge and attitude of health care professionals towards the use of telemedicine in the rural areas of Sindh, Pakistan. Materials and Methods: The cross-sectional study was conducted with participation of 212 healthcare professionals including physicians, consultants, surgeons, residents, dentists, and house officers working in public sector hospitals. Face to face method was used for data collection. Chi square test and logistic regression analysis were applied to find the association of different variables with knowledge and practice of telemedicine using SPSS V 24. Results: The knowledge of participants regarding the usability of telemedicine and various tools used for the provision of medical services (video consultations, conferencing, use of applications, software, online groups) was good, 52.2% showed agreement when they were questioned about being aware of online healthcare service provision. Regarding the practice, 52.8% of the participants had practiced telemedicine by delivering healthcare services through online consultations. The majority of the participants were surgeons (25.9%), residents (23.1%) and physicians (18.9%). The internet (42.4%) and public media (25.9%) were the major sources of information for telemedicine. 70.5 % suggested that strategies and efforts should be directed towards the enhanced implementations of telemedicine. Training in telemedicine as a source of information [OR = 13.02 (95% CI = 3.9-43.6), p < 0.001)] and awareness regarding the effect of telemedicine in healthcare quality [OR = 10.25 (95% CI = 2.9-35.4), p < 0.001)] remain the predicting factors for practice of telemedicine among healthcare workers in multivariate regression analysis. Conclusions: Telemedicine has technologically revolutionized the medical sciences worldwide. The awareness level and usage of telemedicine is good among the health care professionals in rural Sindh. Telemedicine should be utilized to provide quality healthcare in underprivileged areas by investing in the infrastructure, and education.